What is the degree of social disability risk in China under the background of the aging population? Social disability risk measurement index system design and evaluation research based on China - Guo, Qianqian; Sun, Yufeng; Fan, Miao; Li, Zhichun (Frontiers in Public Health, 2023)
The impact of the aging population in China varies between regions. It is because regions with different resource endowments, such as those related to economy, population, and medical care, have different degrees of disability risk in the face of the increases in the disabled and semi-disabled elderly population caused by the overall aging of the population. This study used the Delphi method to construct a social disability risk measurement index system with macro, meso, and micro dimensions. At the same time, based on the data of CHARLS2018, an AHP-entropy method was used to calculate the comprehensive weight of the index, and the standard deviation classification method was used to classify the comprehensive and criterion-level measurement scores of 28 provinces. The regional degree of social disability risk was evaluated and analyzed in subdimensions. Our research indicates that China's social disability risk situation is not promising, with a general medium to high-risk level. The score of degree of social disability risk among provinces is consistent with the regional economic development level to a large extent. The risk of social disability varies significantly among the eastern and central, and western regions of China and the provinces within the three regions.